Effects of Stretch-Bending Straightening on the Tensile Properties of Cold Rolled Packaging Steel - Sebastian Möller; Dimitrios Nouskalis; Björn Ehmke; Dirk Matusch; Christian Dresbach; Holm Altenbach (Metals)
Achieving perfect flatness, tension-free surfaces, and exceptional resistance to spring back are important characteristics of packaging steel, setting the standard for high-quality material performance. To guarantee these crucial parameters, the implementation of the stretch-bending process at the final stage of the production route is indispensable. Besides improving the flatness properties, the induced plastic deformation results in an accompanying change in the mechanical properties. This investigation focuses on understanding this change in mechanical properties due to different stretch-bending straightening process parameters. A multivariate predictive model is created to calculate a process window for achieving the desired flatness and also mechanical properties in the production of packaging steel. This model is validated by experiments with a laboratory facility.